HEALTH-PROMOTING PROPERTIES OF BROAD BEANS (VICIA FABA L.) - Alicja Baranowska (Health Problems of Civilization)
The aim of this work was to review scientific studies on the health-promoting properties of one of the oldest legumes, the broad bean (Vicia faba L). A review of the research literature concludes that broad bean seeds are a rich source of plant proteins, complex carbohydrates, essential vitamins, minerals and phytochemicals. The seeds also contain small amounts of lipids. Broad beans are a good source of l-3,4-dihydroxphenylalanine (L-DOPA), a precursor of dopamine, which is used in the treatment of Parkinson’s disease. GABA (gamma-aminobutyric acid), present in broad beans, is an amino acid that lowers blood pressure. Bean seeds contain anti-nutritional substances, e.g. vicin and convicin, which exacerbate the symptoms of hemolytic anemia known as favaism. Based on scientific evidence, regular consumption of legumes is potentially beneficial to health, including but not limited to reducing the risk of many chronic diseases. There is currently a growing interest in the use of legume proteins for the production of functional food products. Analysis of the research literature suggests that Vicia faba L. seeds can be a functional food ingredient and should be an important part of the diet.